Duloxetine and pregabalin: High-dose monotherapy or their combination?—Study protocol for a randomized trial in patients with postoperative pain after total knee arthroplasty based on the classification of central sensitization inventory scores - Haodong Wu; Shuxin Yao; Yuanchi Huang; Chao Xu; Jianbing Ma (PLoS ONE, 2025)
Background Residual pain after total knee arthroplasty (TKA) often causes patient dissatisfaction. Patients with preoperative central sensitization (CS) are especially susceptible to chronic pain after TKA. Although duloxetine and pregabalin are known to relieve pain in CS patients, there is limited evidence on the precise effectiveness and safety of increasing the dosage or combining these medications. To address this gap, we designed a randomized, triple-blind clinical trial to assess the efficacy and safety of increasing the maximum dosage or combining these drugs for patients who do not respond to standard doses. Methods Patients scheduled to undergo primary unilateral TKA will be screened for CS using the central sensitization inventory (CSI). CS patients will then be randomly assigned to Groups 1–5, while non-CS patients will be assigned to Group 6. All groups will receive multimodal analgesia. Groups 1 and 6 will receive a placebo. During the initial 6-week period, Groups 2 and 3 will take 60 mg/day of duloxetine, while Groups 4 and 5 will take 300 mg/day of pregabalin. Subsequently, non-responders will enter a 6-week period of high-dose/combination therapy. Group 2 will receive 120 mg/day of duloxetine, Group 3 and 4 will receive a combination of 60 mg/day of duloxetine and 300 mg/day of pregabalin, and Group 5 will receive 600 mg/day of pregabalin. The primary outcome will be to compare residual pain intensity at 6 months between the high-dose monotherapy groups (Groups 2, 5 pooled) and the combination therapy groups (Groups 3, 4 pooled), which will be measured using the brief pain inventory (BPI) 24-hour average pain change. Secondary outcomes will assess pain and functionality. Discussion This study aims to evaluate the efficacy and safety of increasing medication to the highest dose or combining two medications in patients with CS who have not responded well to standard doses of duloxetine or pregabalin after TKA. The goal is to provide clinicians with evidence-based recommendations for choosing an appropriate pain management strategy for these patients. Trial registration Chinese Clinical Trial Registry, ChiCTR2400081990. Registered on 18 March 2024.